When politics meets policy: a realist review of how political context shapes the impact of public health legal interventions - Lee, Yuri; Park, Jiwon (Frontiers in Public Health, 2025)
BackgroundPublic health laws—whether focusing on taxation, bans, mandates, or licensing—are powerful tools for reducing risk behaviors and improving population health. However, identical legal interventions often produce starkly different outcomes across jurisdictions. Political and social contexts are increasingly recognized as key determinants of such variability.ObjectiveThis study aimed to examine how and why public health legal interventions succeed or fail under different political circumstances, drawing on a Realist Review approach. We synthesized the interplay between legal epidemiology and political determinants of health to develop a deeper understanding of the mechanisms driving health policy outcomes.MethodsWe followed RAMESES guidelines to identify and analyze 20 empirical studies, policy analyses, and global reports published from 2000 to 2023. We included sources that explicitly addressed both public health law or policy interventions and the political environment (e.g., trust in government, partisanship, lobbying, global donor influence). Using a Context–Mechanism–Outcome (CMO) framework, we coded and synthesized patterns to refine our initial program theory on how legal measures interact with political factors to shape health-related results.ResultsSix recurring CMO patterns emerged. Laws are most effective when stable political leadership and public trust enable robust enforcement and funding. Conversely, fragmented governance or ideological polarization undermines or reverses legal interventions, especially those perceived as infringing personal freedoms (e.g., vaccine mandates, obesity restrictions). Industry lobbying frequently dilutes legislation, while external donor–driven policies can falter without sustained domestic support. Evolving moral and cultural attitudes likewise propel or hinder laws over time. We integrate these findings in a conceptual model demonstrating how political determinants modulate legal mechanisms, ultimately affecting population health outcomes.ConclusionThis Realist Review underscores that legal interventions alone cannot guarantee public health improvements. Rather, their success relies on supportive political contexts, coherent enforcement strategies, and alignment with evolving social values. Policymakers and advocates should anticipate and address political barriers—from partisanship to lobbying to donor dependency—to design and implement resilient, evidence-based public health laws. Future research should refine these insights using mixed-methods case studies and longitudinal evaluations, ensuring policy adaptations that optimize health equity and policy sustainability.